Design Of Mini ECG for High Mobility Athlete - Sugondo Hadiyoso; Achmad Rizal; Koredianto Usman; Radian Sigit (Pusat Penelitian Informatika - LIPI, 2013)
Electrocardiogram (ECG) is signal as a result of the electrical activity of the heart. ECG is taken by placing electrodes at a certain point a person's body. In this research made â€‹â€‹digital ECG device that is used to monitor the condition of the heart of athlete. ECG is designed in small size that can be put on the waist with a mini LCD to view ECG signal graph. The system used 3 ECG leads with Einthoven triangle method. Electrodes are attached to the body taking electrical signal activity of the heart then the signal is amplified and filtered by signal conditioning. By Analog to Digital Converter signals are converted into digital data then the microcontroller reads data from ADC and displays graphs of signal and heart rate on the Nokia 5110’s LCD screen. Keywords: Electrocardiogram, Athlete, Einthoven, ADC, Nokia 5110